ChemInform Abstract: Efficient Synthesis and Antiproliferative Activity of Novel Thioether‐Substituted Flavonoids. Issue 52 (24th December 2013) - Huang, Wei; Chen, Qiong; Yang, Wen‐Chao; Yang, Guang‐Fu
Abstract The synthesis of a broad range of thioether substituted flavonoids from the corresponding flavonoid chlorides is described.